Susceptibility to prosocial and antisocial influence in adolescence. (25th August 2020) - Ahmed, S.; Foulkes, L.; Leung, J.T.; Griffin, C.; Sakhardande, A.; Bennett, M.; Dunning, D.L.; Griffiths, K.; Parker, J.; Kuyken, W.; Williams, J.M.G.; Dalgleish, T.; et al.
ABSTRACT: Introduction: Adolescents are particularly susceptible to social influence and previous studies have shown that this susceptibility decreases with age. The current study used a cross‐sectional experimental paradigm to investigate the effect of age and puberty on susceptibility to both prosocial and antisocial influence. Methods: Participants (N = 520) aged 11–18 from London and Cambridge (United Kingdom) rated how likely they would be to engage in a prosocial (e.g. "help a classmate with their work") or antisocial (e.g. "make fun of a classmate") act. They were then shown the average rating (in fact fictitious) that other adolescents had given to the same question, and were then asked to rate the same behaviour again. Results: Both prosocial and antisocial influence decreased linearly with age, with younger adolescents being more socially influenced when other adolescents' ratings were more prosocial and less antisocial than their own initial rating. Both antisocial and prosocial influence significantly decreased across puberty for boys but not girls (independent of age). Conclusions: These findings suggest that social influence declines with increasing maturity across adolescence. However, the exact relationship between social influence and maturity is dependent on the nature of the social influence and gender. Understanding when adolescents are most susceptible to different types of social influence, and how this might influence their social behaviour, has important implications for understanding adolescent social development.